2006
DOI: 10.1111/j.1365-2311.2006.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of visual and olfactory cues of hosts and non‐hosts by three bark beetles (Coleoptera: Scolytidae)

Abstract: 1. There has been a long-standing pre-occupation with how phytophagous insects use olfactory cues to discriminate hosts from non-hosts. Foragers, however, should use whatever cues are accurate and easily assessed, including visual cues.2. It was hypothesised that three bark beetles, the mountain pine beetle (MPB), Dendroctonus ponderosae Hopkins, the Douglas-fir beetle (DFB), D. pseudotsugae Hopkins, and the western balsam bark beetle (WBBB), Dryocoetes confusus Swaine, integrate visual and olfactory informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 75 publications
5
61
2
Order By: Relevance
“…In conifer bark beetles, visual (Campbell and Borden, 2006) and olfactory cues (e.g., tree volatiles) (Zhang and Schlyter, 2004) were proposed as proximate causes for their host selection. Previous field studies reported an increase in the number of Dendroctonus pseudotsugae beetles attracted to pheromone-baited traps when the volatiles of their own host trees were used as the kiromone (Pureswaran and Borden, 2005).…”
Section: Proximate Causes For Host Selectionmentioning
confidence: 99%
“…In conifer bark beetles, visual (Campbell and Borden, 2006) and olfactory cues (e.g., tree volatiles) (Zhang and Schlyter, 2004) were proposed as proximate causes for their host selection. Previous field studies reported an increase in the number of Dendroctonus pseudotsugae beetles attracted to pheromone-baited traps when the volatiles of their own host trees were used as the kiromone (Pureswaran and Borden, 2005).…”
Section: Proximate Causes For Host Selectionmentioning
confidence: 99%
“…However, all these cues vary in both their cost of assessment and accuracy, and some cues can be more reliable than others (Fawcett & Johnstone, 2003). For example, vision plays a role in host plant location of some herbivorous beetles (Tanton, 1977;Hausmann et al, 2004), but visual cues may be 1 Journal of Insect Behavior (2007) 20:247-266 less accurate in complex vegetation than in open stands (Rausher, 1981;Endler, 1993;Campbell & Borden, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Specific volatile terpenoids are used by the beetles as cues in host identification and selection, in combination with other visual and olfactory cues from both host and non-host plants (Andersson et al 2009;Campbell and Borden 2006a;Campbell and Borden 2006b). Because the exact relationship between the spruce bark beetle and most host terpenoids is unknown it is difficult to predict accurately how qualitative differences in terpene chemistry will affect beetle colonization biology (Erbilgin et al 2007b).…”
Section: The Concentration Of Individual Terpenoids In Constitutive Bmentioning
confidence: 99%